1999
DOI: 10.1051/rnd:19990410
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of catecholamines, ascorbic acid, progesterone and oxytocin in the corpora lutea of cyclic and pregnant cattle

Abstract: -To determine if there are inter-relationships between progesterone, oxytocin (OT), dopamine (DA), noradrenaline (NA) and ascorbic acid, these compounds were measured in the corpus luteum (CL) from cattle at different stages of the oestrous cycle (n = 42) and from 1-5 months of pregnancy (n = 27). They were measured by radioimmunoassay (RIA), high performance liquid chromatography (HPLC) and colorimetric methods. Corpora lutea were collected from heifers and cows within 30 min of slaughter on days 1-5, 6-10, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
4
12
0
Order By: Relevance
“…Moreover, the concentrations of dopamine and NA in the developing CL (Days 3-5 of the estrous cycle) are 3-5 fold higher than in the mid-luteal phase (Fig. 1) [83]. Our findings agree with the data of Pesta et al [90] that β-adrenergic binding and ligand affinity for the β-receptor in bovine CL were highest on Day 4 of the estrous cycle and then gradually decreased to the end of the luteal phase.…”
Section: Noradrenaline As a Luteotropic Factorsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the concentrations of dopamine and NA in the developing CL (Days 3-5 of the estrous cycle) are 3-5 fold higher than in the mid-luteal phase (Fig. 1) [83]. Our findings agree with the data of Pesta et al [90] that β-adrenergic binding and ligand affinity for the β-receptor in bovine CL were highest on Day 4 of the estrous cycle and then gradually decreased to the end of the luteal phase.…”
Section: Noradrenaline As a Luteotropic Factorsupporting
confidence: 91%
“…However, direct contact of adrenergic nerve fibers with luteal and granulosa cells has not been observed in any mammalian species [78,79]. Although the concentrations of NA and its precursor dopamine are 10-and 100-fold lower in bovine CL than in ovarian stroma, respectively [81], the high correlation between dopamine and NA contents [81][82][83] and the presence of dopamine-β-hydroxylase in bovine CL [84] suggest de-novo synthesis of NA in this tissue (Table 1). Condon and Black [85] demonstrated that catecholamines stimulate P4 secretion in bovine CL in vitro.…”
Section: Noradrenaline As a Luteotropic Factormentioning
confidence: 98%
“…Considering that NA released at the ovarian level by the oestrogenic ganglionic stimulus might be responsible for the increase in ovarian P 4 , the findings of this study are in agreement with postulations by Hsueh et al (1984) and Miszkiel et al (1999) that NA stimulates the activity of 3b-HSD. At the same time, P 4 produced by NA stimulus reduces the activity of monoaminooxidase (MAO) and catechol-O-methyl-transferase, the enzymes primarily responsible for the degradation of catecholamines (Mannisto & Kaakkola 1999, Eisenhofer et al 2004.…”
Section: Discussionsupporting
confidence: 93%
“…During lactation, here is an extra need for glucose to serve as a precursor for lactose synthesis, which is reflected by low plasma glucose. In cattle, at different stages of estrus and pregnancy, Miszkiel et al [74] found that ascorbic acid concentrations were directly correlated with those of progesterone, she camels in estrus were found to have increased ascorbic acid levels in plasma and total leukocytic count. In contrast to our findings, Naziroğlu and Gür [75] did not find any difference between pregnant and non-pregnant cows with respect to plasma ascorbic acid.…”
Section: Resultsmentioning
confidence: 99%